Recent biodiversity changes in grasslands across elevational bands in Switzerland - Häberlin, Kathrin E.R.; Dengler, Jürgen (Basic and applied ecology, 2025)
Concerns about intensification of land use and land abandonment threatening plant diversity called for the establishment of national monitoring and agri-environmental payment schemes in Switzerland. Yet, little is known about recent biodiversity changes in Swiss grasslands. The analyses in this study were based on the presence / absence records of 455 permanent 10 m2 plots in grasslands systematically spread across elevational bands in Switzerland, collected by the Swiss Biodiversity Monitoring BDM. We assessed changes in vascular plant species richness, mean ecological indicator values and species composition at the local scale in Swiss grasslands over two decades (2001–2023) and for three elevational sets (all, below, and above 1200 m a.s.l.). Further, we identified winners and losers at the species level. Throughout all three elevational sets, we found that the mean species richness increased in the study period. Likewise, the mean ecological indicator values for temperature increased throughout. While the mean ecological indicator values of nutrient, soil moisture and reaction remained constant for the set of all plots, at lower elevations there was a trend towards a decreased nutrient value whereas soil moisture decreased at higher elevations. Overall, more species showed positive rather than negative trends over time. Especially at lower elevations, short-lived, ruderal species and C4 grasses are on the increase. We suggest that these trends are linked to the increased harvesting frequency and the recent trend towards longer dry spells in Swiss summer. By contrast, at higher elevations, stress tolerance of grasslands decreased while competitiveness increased. These diverging patterns point to different drivers of biodiversity change dependent on elevation and call for context-dependent conservation measures.